Effects of Pre-discharge Program for Surgical Wound Care and Infection Prevention among Patients in the Private Surgery Ward of Buddha Sothorn Hospital, Chachoengsao Province - Thamutok, Sunsanee; Tongsubanan, Sirilux; Wanthaneeyakul, Thanidawan; Nitirat, Pornruedee; Manorath, Prapaporn (Journal of Phrapokklao Nursing College, Chanthaburi, 2018)
This quasi-experimental study was based on a one group pretest-posttest design. It aimed to evaluate the effects of the pre-discharge program for surgical wound care and infection prevention on knowledge about and attitude toward surgical wound care among patients in the private surgery ward of Buddha Sothorn Hospital, Chachoengsao Province. Samples were 30 patients aged over 15 years old who admitted in the private surgery ward and had a clean or clean-contaminated surgical wound that needed continuous care at home by patients themselves before the suture removal. Before the samples were discharged from the hospital, they were required to participate in the 2-section program for surgical wound care and infection prevention. Data collection tools developed by a researcher team consisted of a questionnaire to evaluate knowledge about surgical wound care (KR-20 = .57) and a questionnaire to evaluate attitude toward surgical wound care (α = .70). Also, an evaluation form to determine wound infection was used. The intervention was conducted from December 2014 to February 2015. Data were collected before and after implementing the program as well as in 2 weeks later. Statistics used for data analysis included frequency, percentage, mean, standard deviation, repeated one-way ANOVA, and multiple comparison by Bonferroni method. The results revealed that: 1. After participating in the program and in 2-week follow up, samples’ knowledge about surgical wound care was significantly higher than before participating in the program (MD = 2.50, p < .001 and MD = 2.87, p < .001, respectively). However, samples’ knowledge after participating in the program and in 2-week follow up were not significantly different. 2. Before and after participating in the program, samples’ attitude toward surgical wound care was not significantly different. In contrast, in 2-week follow up, samples’ attitude toward surgical wound care was significantly higher than those before (MD = 3.16, p < .001) and after participating in the program (MD = 2.23, p < .05). 3. After implementing the program, there was no incidence of surgical wound infection among the samples. This study suggested that the pre-discharge program for surgical wound care and infection prevention should be fostered in the hospital in order to promote surgical wound care among patients and reduce the incidence of surgical wound infection.